PENGARUH BEBAN KERJA TERHADAP KINERJA KARYAWAN MELALUI BURNOUT SEBAGAI VARIABEL MEDIASI - Sholehah, Nurul Hidayatus; Lailiyah, Elliv Hidayatul (KOLEGIAL, 2023)
Human resources are important in a company. Human resources play an important role in providing services, so that the success or failure of a company is determined by its human resources. This study aims to determine the effect of workload on employee performance with burnout as a mediating variable at Fatimah Hospital in Lamongan, East of Java. The instrument used is a questionnaire. The population in this study were employees of Fatimah Hospital. A sample of 63 respondents was determined by probability sampling with a simple random sampling approach. The analyzed data used in this study is path analysis using the SPSS application program. The results showed that workload has a positive effect on bournout. Workload has a negative effect on employee performance. Bournout has a negative effect on employee performance. Burnout mediates the effect of workload on employee performance at Fatimah Hospital.